Pengaruh Pemahaman Akuntansi dan Pengalaman Kerja Aparatur Terhadap Penyusunan Laporan Keuangan Daerah Pada Pemerintah Kota Banda Aceh - Evri Yenni (Jurnal EMT KITA, 2017)
The purpose of this study is to examine the effect of understanding of accounting and work experience of the apparatus towards the preparation of local financial statements either simultaneously or partially. This research was conducted at the Regional Device Work Unit (SKPD) Kota Banda Aceh. Respondents of this study include Administration Officials (PPK) and Assistant Financial Administration Officials (PPK Assistant) with the number of 78 respondents. This research uses census method while the analysis tool used is multiple linear regression. The results showed that the understanding of accounting and work experience apparatus either simultaneously or partially affect the preparation of local financial statements Banda Aceh.